Post‐Deformation Microstructure and Texture Characterization of Fe–18Mn–0.6C–1.5Al TWIP Steel. Issue 12 (16th March 2015) - Peng, Ching‐Tun; Callaghan, Mark D.; Li, Huijun
Abstract : The superior features of high manganese TWIP steels under deformation are believed to be originated from the induced twinning boundaries acting as barriers, hence impeding the activity of dislocation slips. We investigate the effect of different deformation mechanisms and grain orientation on mechanical twinning in a low stacking fault energy, Fe–18Mn–0.6C–1.5Al TWIP steel, using microstructure characterization by electron back‐scattered diffraction. Samples were deformed at room temperature in tension and in compression with various strain rates at different strains. The microstructure revealed that under the same amount of deformation, the smaller grain size was found and less twinning boundaries were disclosed in compression. Texture measurements showed that grains strongly oriented to <1 1 1> fiber parallel to the tensile axis when subjecting to tensile loading, while in compression, the brass type component was mainly observed. Abstract : The effect of different deformation mechanisms and grain orientation on mechanical twinning in a Fe–18Mn–0.6C–1.5Al TWIP Steel has been investigated, using microstructure characterization by electron back‐scattered diffraction. Samples are deformed in tension and in compression with various strain rates at different strains. Under the same amount of deformation the less twinning boundaries are disclosed in compression.